Increase in Marriage Dispensation at the Giri Menang Religious Court West Lombok NTB - Lina Turrifkiah (JURNAL PENDIDIKAN IPS, 2024)
Marrying underage is highly discouraged considering the many negative impacts that can be caused. considering the many negative impacts that can be caused. Starting from problems health, mental readiness, emotional maturity, economy to the way of thinking. In Article 7 of Law Number 16 of 2019 concerning marriage is explained in Paragraph 1 which reads Marriage is only permitted if the man and woman have reached the age of 19 years. Reach the age of 19 years. However, if someone wants to get married, the man and woman have not reached the age specified by the law, it is permissible to apply for marriage dispensation at the Religious Court. This research focuses on the issue of the procedure for applying for marriage dispensation and what are the factors behind the rampant the background of the rampant submission of marriage dispensation, and what are the considerations of judges Giri Menang Religious Court in granting dispensation of marriage. This study uses a qualitative field research method. Data collection techniques using observation methods, interviews and documentation, and analyzed qualitatively. Findings in this study it is known that the Panel of Judges when granting dispensation. Due to several factors including factors of pregnancy outside of marriage, length of courtship, and elopement (selarian) then refers to the dharuri the benefit that is dharuriyah for the applicant, namely in terms of maintaining the soul and offspring. preserving the soul and offspring